Modelling framework for integration of large-scale heat pumps in district heating using low-temperature heat sources - Henrik Pieper; Vladislav Mašatin; Anna Volkova; Torben Ommen; Brian Elmegaard; Wiebke Brix Markussen (International Journal of Sustainable Energy Planning and Management, 2019)
The paper presents a modelling framework that may be used to plan the integration of large-scale HPs in district heating (DH) areas. By use of the methodology both optimal HP capacities to be installed and optimal choice of heat source to be used during the year are identified by minimizing total cost of ownership including investment and operational costs. The modelling framework uses mixed-integer linear programming and hourly calculations over one year. Seasonal variations of the heat source temperatures, capacity limitations and HP coefficient of performance as well as technical constraints were taken into account.